Divergent Effects of Haloperidol on Motor Versus Spatial Functions - Robert Lalonde; Catherine Strazielle (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2017)
Parkinson's disease causes motor and non-motor deficits mitigated at different degrees with dopamine replacement therapy [1-3]. In addition to the cardinal symptoms of muscle rigidity, akinesia, and resting tremor, patients with Parkinson's disease display postural instabilities. In particular, patients fall more often than controls [4]. More worrisome are the findings that patients' loss in postural control respond poorly to the primary treatment, l-dopa [5], and that l-dopa even impaired some aspects of it [6]. Motor and non-motor deficits have been reproduced in genetic models of Parkinson's disease [7], or after injections of neurotoxic agents that deplete dopamine concentrations in striatum [8]. Moreover, parkinsonian symptoms appear in schizophrenic subjects after high doses of dopamine-2 (D2) receptor antagonists such as chlorpromazine (CPZ) and haloperidol, to a lesser extent the more selective D4 receptor antagonist, clozapine [9]. In the present study, motor and non-motor effects of haloperidol were examined in mice for exploratory activity in open-field [10], elevated plusmaze [11,12], and emergence [13] tests, motor coordination in stationary beam, coat-hanger, and rotorod [14] tests, and spatial learning in the Morris water maze [15,16].